An investigation of the Nernst?Planck model of an electro-viscous fluid flow between squeezing plates with homogeneous?heterogeneous reactions - Jan W.U.; Farooq M.; Shah R.A.; Khan A.; Jan R.; Alrashedi Y. (Springer Science and Business Media Deutschland GmbH, 2025)
The significant influence of convective transport flow between compressing plates involving both homogeneous and heterogeneous reactions, with uniform ionic distribution across the plates? surfaces, is examined. The physical situation is elucidated through the utilization of fundamental equations governing fluid flow, including the Poisson?Boltzmann equation, the energy equation, and the Nernst?Planck equation, as well as equations pertaining to heterogeneous and homogeneous reactions. The governing equations undergo a transformation into systems of ODEs through a similarity transformation. These equations are then solved numerically utilizing the BVP4c technique for different controlling parameter values, and the outcomes are tabulated and visually represented. In addition, a homotopy analysis method (HAM) is employed to solve the resulting equations. The accuracy and validity of the HAM findings are confirmed by comparing them to solutions obtained from BVP4c numerical solver packages. Based on both homogeneous and heterogeneous chemical reactions, it is concluded that compressing plates increases the distribution of anions and cations. Physical restrictions impact vertical and horizontal velocities, as well as positive and negative charge profiles, are drawn and briefly described. Furthermore, the rate of vertical velocity near the parallel plates increases with an increase in the squeezing Reynolds number. ? The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature 2024.